Pengaruh Senam Hamil Terhadap Lama Kala Dua dan nilai APGAR skore Bayi Baru Lahir pada ibu primigravida di desa Tegalan wilayah kerja BPS Ny. Ninghola Kandat Kabupaten Kediri. - LESTARI, INDAH (JURNAL KEPERAWATAN SEHAT, 2011)
One reason for the high maternal and perinatal mortality in Indonesia is the result of a long labor. It is still the highest cause is the bleeding factor, but the incidence of prolonged labor also common and impact on maternal and fetal mortality. Pregnancy exercise is an exercise program for healthy pregnant women to prepare the physical condition of the mother by taking care of the muscles and joints that play a role in the delivery process. The purpose of this study is to prove whether pregnancy exercise can speed up the second period of labor time and improve the value of newborn APGAR scores. This study is an experimental study with a sample of pregnant primigravidaewho are in the working area of the Ninghola midwife and perform the ANC in her labor clinic. From 24 samples that have gestation age 24-28 weeks, only 20 respondents who include in the criteria, could be evaluated; 10 samples that have pregnancy exercise until just before birth (cases) and 10 other samples without pregnancy exercise (control). Labor process is followed until delivery. The results obtained, there is a relationship between pregnancy exercise and the duration of second period of labor, with the results of t test, p = 0.000 and there is a relationship between pregnancy exercise and the newborn APGAR scores, with test results exsact fisher that no difference between the two groups with p = 0.342. This is because pregnancy exercise can enhance and improve the circulatory system, especially into the muscles to increase strength and muscle tone;. it is also to increase blood circulation to the uteroplacental thus improves the growth of the muscles of the uterus and intrauterine fetal development. The optimal growth of the uterine muscles will cause uterine contractions more optimal and coordinated at the time of delivery. Exercise during pregnancy give a positive effect on the opening of the cervix and coordinated uterine activity during labor.Keywords: pregnancy exercise, APGAR scores, length of labor